Diamond nanoparticles suppress lateral growth of bacterial colonies - Lišková, Petra; Beranová, Jana; Ukraintsev, Egor; Fišer, Radovan; Kofroňová, Olga; Benada, Oldřich; Konopásek, Ivo; Kromka, Alexander (Colloids and surfaces. B, Biointerfaces, 2018)
Diamond nanoparticles (DNPs) of various types have been recently reported to possess antibacterial properties. Studies have shown a decrease of the colony forming ability on agar plates of the bacteria that had been previously co-incubated with DNPs in the suspension. Before plating, bacteria with DNPs were adequately diluted in order to obtain a suitable number of colony forming units. However, residual DNPs were still present on an agar plate, concentrated on the surface during the plating process; this introduces a potential artifact which might affect colony growth. The effect of DNPs remaining on the surface, alongside growing bacteria, has not been previously investigated. In this work, we present the experiments designed to investigate the effect of DNPs on bacterial survival and on the growth of the bacterial colony on a solid media. We employed Escherichia coli and Bacillus subtilis as models of Gram-negative and Gram-positive bacteria, respectively, and Proteus mirabilis as a model of bacterium exhibiting swarming motility on the surfaces. We analyzed the number, area, and weight of bacterial colonies grown on the agar surface covered with DNPs. We did not observe any bactericidal effect of such applied DNPs. However, in all bacterial species used in this work, we observed the appreciable reduction of colony area, which suggests that DNPs obstruct either bacterial growth or motility. The most obvious effect on colony growth was observed in the case of motile P. mirabilis. We show that DNPs act as the mechanical barrier blocking the lateral colony growth.
Keywords: Bacillus subtilis; vztah mezi dávkou a účinkem léčiva; velikost částic; diamant; mikrobiální testy citlivosti; Escherichia coli; Particle Size; Nanoparticles; povrchové vlastnosti; Structure-Activity Relationship; Proteus mirabilis; Anti-Bacterial Agents; Diamond; nanočástice; Microbial Sensitivity Tests; Dose-Response Relationship, Drug; Bacteria; vztahy mezi strukturou a aktivitou; antibakteriální látky; Surface Properties